Protein phosphatase 5 regulates titin phosphorylation and function at a sarcomere-associated mechanosensor complex in cardiomyocytes - Krysiak, Judith (Nat Commun, 2018)
Serine/threonine protein phosphatase 5 (PP5) is ubiquitously expressed in eukaryotic cells; however, its function in cardiomyocytes is unknown. Under basal conditions, PP5 is autoinhibited, but enzymatic activity rises upon binding of specific factors, such as the chaperone Hsp90. Here we show that PP5 binds and dephosphorylates the elastic N2B-unique sequence (N2Bus) of titin in cardiomyocytes. Using various binding and phosphorylation tests, cell-culture manipulation, and transgenic mouse hearts, we demonstrate that PP5 associates with N2Bus in vitro and in sarcomeres and is antagonistic to several protein kinases, which phosphorylate N2Bus and lower titin-based passive tension. PP5 is pathologically elevated and likely contributes to hypo-phosphorylation of N2Bus in failing human hearts. Furthermore, Hsp90-activated PP5 interacts with components of a sarcomeric, N2Bus-associated, mechanosensor complex, and blocks mitogen-activated protein-kinase signaling in this complex. Our work establishes PP5 as a compartmentalized, well-controlled phosphatase in cardiomyocytes, which regulates titin properties and kinase signaling at the myofilaments.